ZGT 374E/3- Remote Sensing - February - March 2004 - PPSF, Pusat Pengajian Sains Fizik (2004)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2003/2004 February/March 2004 ZGT 374E/3- Remote Sensing [Penderiaan Jauh] Duration: 3 hours [Masa: 3 jam]